Injury risk factors in female European football. A prospective study of 123 players during one season - Ostenberg, A.; Roos, H. (Scandinavian Journal of Medicine & Science in Sports, 2000)
The purpose of this study was to register prospectively the injuries in female soccer and to study their correlation to potential risk factors. A total of 123 senior players from eight teams of different levels were followed during one season. Isokinetic knee muscle strength at 60 and 180 degrees/s, one-leg-hop, vertical jump, square-hop, and continuous multistage fitness test (MFT) were tested at the end of the pre-season. In addition, Body Mass Index (BMI) and general joint laxity were measured. During the season, April-October, all injuries resulting in absence from one practice/game or more were registered. Forty-seven of the 123 players sustained altogether 65 injuries. The total injury rate was 14.3 per 1000 game hours and 3.7 per 1000 practice hours. The knee (26%) was the most commonly injured region followed by the foot (12%), ankle (11%), thigh (11%) and back (11%). The risk of sustaining moderate and major injuries increased in the later part of the game or practice. Significant risk factors for injuries were an increased general joint laxity (odds ratio (OR)=5.3, P<0.001), a high performance in the functional test square-hop (OR=4.3, P=0.002), and an age over 25 years (OR=3.7, P=0.01). The injury rate was not different compared to male soccer, but knee injuries were more common, which is in accordance with previous studies. None of the risk factors identified in this study is easily applicable for future intervention studies in the attempts to reduce the injury rate in female soccer.